CD70 recruitment to the immunological synapse is dependent on CD20 in B cells - Abbey B. Arp; Andrea Abel Gutierrez; Martin ter Beest; Guus A. Franken; Harry Warner; Andrea Rodgers Furones; Angelique N. Kenyon; Franziska Jäger; Alfredo Cabrera-Orefice; Kathrin Kläsener; Sjoerd van Deventer; Lenny Droesen; et al. (Proceedings of the National Academy of Sciences, 2025)
CD20 is a four-transmembrane protein expressed at the surface of B cells from late pro-B cells to memory B cells, with the exception of plasma cells. Its expression pattern makes it an attractive therapeutic target for different B cell malignancies and autoimmune diseases. Despite the clinical success of CD20-targeting antibodies, the biology of the CD20 protein is still not well understood. We investigated CD20 binding partners in the membrane of human B cells using immunoprecipitation followed by mass spectrometry analysis. We identified a molecular interaction between CD70 and CD20, and confirmed this using proximity ligation assays. CD20–CD70 spatiotemporal colocalization was validated at the plasma membrane of B cells using high-resolution microscopy. Cell surface expression of CD70 was found to be enhanced upon CD20 overexpression, suggesting a role for CD20 in stabilizing CD70 at the B cell membrane. Moreover, we observed impaired B-T cell synapse formation and defective recruitment of CD70 to the immunological synapse in the absence of CD20. Impaired synapse formation was confirmed by deleting CD20 in primary B cells, and analysis of B cells from a CD20-deficient patient. Finally, CD20-deletion resulted in diminished T cell activation and cytokine secretion. Together, this study demonstrates that CD20 interacts with CD70 at the B cell membrane, and that CD20 is required for immune synapse formation between B and T cells and consequent T cell activation.